1998
DOI: 10.1210/jc.83.7.2576
|View full text |Cite
|
Sign up to set email alerts
|

Normal Growth Hormone Secretory Reserve in Men with Idiopathic Osteoporosis and Reduced Circulating Levels of Insulin-Like Growth Factor-I

Abstract: Many men with idiopathic osteoporosis have reduced circulating insulin-like growth factor-I (IGF-I) levels. The major source of circulating IGF-I is GH-mediated production by the liver. The known anabolic effects of GH on the skeleton raised the possibility of GH deficiency in these men. We sought to test this hypothesis in this study. Fourteen men (mean age, 52.1 +/- 3.2 yr, range 31-68) with idiopathic osteoporosis were studied. Mean lumbar spine bone mineral density (BMD) was 0.723 g/cm2, T score -3.5; femo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0
5

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 0 publications
1
32
0
5
Order By: Relevance
“…Modification of the IGF system has been reported in patients infected with HIV. (20) We measured only IGF1 that has been shown to be decreased in males with idiopathic osteoporosis, (21) and we observed no changes in our HIV ϩ patients. Most of the studies of BMD in HIV ϩ patients have included only a small proportion of untreated patients or none at all.…”
Section: Ameil Et Almentioning
confidence: 57%
“…Modification of the IGF system has been reported in patients infected with HIV. (20) We measured only IGF1 that has been shown to be decreased in males with idiopathic osteoporosis, (21) and we observed no changes in our HIV ϩ patients. Most of the studies of BMD in HIV ϩ patients have included only a small proportion of untreated patients or none at all.…”
Section: Ameil Et Almentioning
confidence: 57%
“…Two pa- crease in bone density and decrease fracture rate, but never allow a full recovery of bone architecture [10]. Idiopathic osteoporosis has been related to low insulin-like growth factor 1 (IGF-1) concentrations in blood [3,6] and boné [2], and to osteoblastic dysfunction, leading to limited bone formation whatever the rate of bone resorption [19]. Thus, even the patients with IO and normal serum IGF-1 could benefit from bone anabolic drugs.…”
Section: Resultsmentioning
confidence: 99%
“…Both phenomena have been related to low concentrations of insulin-like growth factor 1 (IGF-1) in serum [3,4] and boné [5], and histomorphometric analysis show decreased osteoblastic surface and function [5,6]. Rosen et al found an association of low serum IGF-1 and homozygosity for a specific allele of the IGF-1 microsatellite (192/192) in men with idiopathic osteoporosis [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Esses trabalhos apontam para um importante papel do IGF1 circulante na aquisição do pico de massa óssea e na homeostase esquelética do indivíduo adulto. Entretanto, não parece haver defeito na secreção do GH nos homens com osteoporose idiopática, como constatado por Kurland et al (21) . Estes autores avaliaram 14 homens com osteoporose idiopática após teste de estímulo com arginina e L-dopa, encontrando um padrão secretório normal do GH, apesar de níveis séricos de IGF1 baixos, demonstrando que estes homens não eram deficientes de GH.…”
Section: Eixo Gh/igf1unclassified